Physisch-geographische Beobachtungen im nordwestindischen Trockengebiet: Ein erster Forschungsbericht - Rathjens, Carl (ERDKUNDE, 1957)
During the spring of 1956 the author was able to make observations in some branches of physical geography in the arid zone of north-western India (western Rajasthan and Saurashtra). The great Indian desert (Tharr) and its borderlands are situated on the southern side of the dry belt of the northern hemisphere; they show distinct summer rains, which exercise a pro nounced influence on the landforms of the country. Wide regions of the desert are without a run-off, the Sambhar Lake and other dry basins have large salt deposits. Areal planation by sheet erosion is the predominating element of the landscape. In the Aravelli mountains we find the type of tropical inselbergs (bornhardts) within the borders of the monsoon forest, and further to the west the type of rock cones with piedmont slopes and alluvial veneers, the residual mountains of the arid climate. In several re gions the phenomena of scarplands (cuestas) are widely developed. The sand dunes of the Tharr were built up by south-westerly winds; they are long barchans, and under present conditions are covered and fixed by vegetation. Below the sand of the dunes and in the borderlands of the Tharr there exist eolian sediments (loess), in which the horizons of calcareous concretions (kunkur) have been formed. In the Tharr proper we find grey desert soils, up to the Aravallis and in Saurashtra black cotton soil; only in the region of Mount Abu and in Southern Saurashtra with a rainfall of more than 800 mm. we find also tropical red soils. There is no evidence of a pluvial period corresponding to the last glacial period of the Pleistocene. But there must have been a period of climate drier than today during which the sand of the Tharr was moving and the big dunes were formed. This dry period occurred during postglacial times and may even have extended into historical times so that it would not be correct to speak of a progressive desiccation of north-western India since that time. The influence of man on the development of vegetation and landforms has been very strong, especially through overgrazing, cutting of trees (lopping of Prosopis) and agriculture based on monsoon rainfall. Many features of the present desert conditions have been caused by human intervention over a long period, and the Tharr may thus be called a man-made desert.